Heart failure-induced skeletal myopathy in spontaneously hypertensive rats - Damatto, R. L. [UNESP] (2013)
Background: Although skeletal muscle atrophy and changes in myosin heavy chain (MyHC) isoforms have often been observed during heart failure, their pathophysiological mechanisms are not completely defined. In this study we tested the hypothesis that skeletal muscle phenotype changes are related to myogenic regulatory factors and myostatin/follistatin expression in spontaneously hypertensive rats (SHR) with heart failure. Methods: After developing tachypnea, SHR were subjected to transthoracic echocardiogram. Pathological evidence of heart failure was assessed during euthanasia. Age-matched Wistar-Kyoto (WKY) rats were used as controls. Soleus muscle morphometry was analyzed in histological sections, and MyHC isoforms evaluated by electrophoresis. Protein levels were assessed by Western blotting. Statistical analysis: Student's t test and Pearson correlation. Results: All SHR presented right ventricular hypertrophy and seven had pleuropericardial effusion. Echocardiographic evaluation showed dilation in the left chambers and left ventricular hypertrophy with systolic and diastolic dysfunction in SHR. Soleus weight and fiber cross sectional areas were lower (WKY 3615±412; SHR 2035±224 μm2; P < 0.001), and collagen fractional volume was higher in SHR. The relative amount of type I MyHC isoform was increased in SHR. Myogenin, myostatin, and follistatin expression was lower and MRF4 levels higher in SHR. Myogenin and follistatin expression positively correlated with fiber cross sectional areas and MRF4 levels positively correlated with I MyHC isoform. Conclusion: Reduced myogenin and follistatin expression seems to participate in muscle atrophy while increased MRF4 protein levels can modulate myosin heavy chain isoform shift in skeletal muscle of spontaneously hypertensive rats with heart failure. © 2012 Elsevier B.V.